Proceso de importación para la empresa casa Hyundai que comercializa repuestos accesorio y autopartes para vehículos provincia de El Oro - Chalaco Loja, Cesar Augusto (2015)
This project aims to be a serious proposal that will serve as support for the growth of a nascent company. This is based on a solid and actual knowledge. After analyze various factors that come together to reach the following conclusion: This project can be applied as long as the necessary financial adjustment measures were taken, or find external financing sources or through companies associations.